An exploration of the perceptions of emergency department nursing staff towards the role of a domestic abuse nurse specialist: a qualitative study - McGarry, Julie; Nairn, Stuart (Elsevier, 2015)
There is a clear body of evidence which indicates that a substantial number of people who have experienced domestic violence and abuse attend the emergency department (ED). However, many individuals do not receive effective identification or support. The present study sought to explore the perceptions of ED staff about the perceived value and utilisation of a new domestic abuse nurse specialist role that has been created in one ED in the UK. A qualitative design was used and involved sixteen in-depth interviews with a range of practitioners. The findings highlight that staff highly valued the role of the nurse specialist as one which offered support both professionally and personally. However, the study has also drawn attention to the conundrum that surrounds identification and management of abuse and of enquiry more generally. The ED is ideally suited to identify at risk individuals but is not institutionally organised in a way that prioritises the social concerns of their patients and this nursing role is one way that this issue can be addressed. In light of recent UK and global policy directives further research is needed to explore the development and implementation of identification, management and support in the future.